Собеседования: [сборник] / С. П. Залыгин - Залыгин Сергей Павлович (Писатель - молодежь - жизнь, 1982)
Экземпляры: КХ (20170419) / Инвентарный номер: 770117 / Сис.шифр: 8 / Авт.знак: З-24 / ГРНТИ: 17 / ББК: 83